Overview of Human Resource Management in Islamic Economics - Nurwan, Nurwan; Hamid Habbe, Abdul; Wahab, Abdul (Dinasti Publisher, 2021)
Islamic economic human resources are said to be important because Islamic economic resources must have morals, skills and competencies. The purpose of this study is to review how the concept of human resource management in Islam is.The data collection method in the article is a literature study with descriptive analysis. The results of the study stated thatHuman resources in Islam are those who have the noble qualities of the Prophet SAW, namely Siddiq (true and honest), Amanah (honest/trustful, responsible), Fathanah (intelligent) and Tabligh (transparent). These qualities will produce human resources who are kafa'ah (professional), amanah (trustworthy), and himmatul amal (work motivation).